Analysis of the Interrelation of Speed and High-Speed Endurance in 14-17 Years of Football Players - Shokhrukh Sh. Erkinov (Institute of Medico-legal Publications Pvt Ltd, 2020)
In the analysis of the optimal interrelation between the general and special high-speed physical qualities ofyoung footballers of 14-17 years old, normative tests were used to measure speedy physical performance.It was determined the optimal age group in the test analysis processes of general and special speedyperformance young group footballers.